2015
DOI: 10.1103/physrevb.92.094515
|View full text |Cite
|
Sign up to set email alerts
|

Tetragonal magnetic phase inBa1xKxFe2As2from x-ray and neutron diffraction

Abstract: Combined neutron and x-ray diffraction experiments demonstrate the formation of a lowtemperature minority magnetic tetragonal phase in Ba0.76K0.24Fe2As2 in addition to the majority magnetic, orthorhombic phase. The coincident enhancement in the magnetic ( 1 2 1 2 1) peaks shows that this minority phase is of the same type that was observed in Ba1−xNaxFe2As2 (0.24 ≤ x ≤ 0.28), in which the magnetic moments reorient along the c-axis. This is evidence that the tetragonal magnetic phase is a universal feature o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 17 publications
8
83
1
Order By: Relevance
“…31 we reported a similar behavior in the Ba 1−x K x Fe 2 As 2 compound and attributed the extra influence as due to possible localized defects in parts of the sample. Since then, theory has shown that impurity scattering can play a significant role in the stabilization of the C 4 phase.…”
Section: W E I G H T E D P H a S E F R A C T I O Nsupporting
confidence: 55%
See 4 more Smart Citations
“…31 we reported a similar behavior in the Ba 1−x K x Fe 2 As 2 compound and attributed the extra influence as due to possible localized defects in parts of the sample. Since then, theory has shown that impurity scattering can play a significant role in the stabilization of the C 4 phase.…”
Section: W E I G H T E D P H a S E F R A C T I O Nsupporting
confidence: 55%
“…A similar combined magnetic, structural and superconducting transition for Ba 0.74 K 0.26 Fe 2 As 2 has been reported and this behavior indicates the strong competition between superconduc-tivity and the magnetic C 4 phase. 14,31 While, such a C 2 re-entrance has been reported in Ba 1−x K x Fe 2 As 2 (Reference 31) and its significance discussed (Reference 14), it has not been seen in any other 122 system as far as the authors of this paper are aware. It is not obvious why Ca 1−x Na…”
Section: W E I G H T E D P H a S E F R A C T I O Nmentioning
confidence: 66%
See 3 more Smart Citations